Teachers’s attachments to their place of work and their working locality. A case study of geography teachers in the Silesian Voivodeship (Poland) - Dacy-Ignatiuk Katarzyna; Hibszer Adam (Environmental & Socio-economic Studies, 2019)
The authors of the article sought to answer the questions: do geography teachers feel a tie with their place of work, what is the strength of this relationship and what factors influence these declared ties with the place. A step towards knowing the answers is the declared subjective assessment of emotional relationships with such a place. To this end, surveys were conducted among geography teachers. Due to their profession, they are a social group having a wide range of influence on young people and their attitudes towards their local geographical environment. Organizational reasons (the ability to reach teachers of all schools through the information exchange platform between Board of Education and school heads – so-called the headmasters panel) decided to examine a selected group of respondents – geography teachers of the Silesian Voivodeship. Google questionnaire was used as an electronic form of data collection. The research was quantitative and only partly qualitative. The analysis of the obtained results gave an interesting view of the perception of teachers' relations with the place where their school is located – their place of work. Almost all respondents declared the existence of a territorial bond with their place of work. The workplace itself is an important factor in the formation and strength of these ties. The length of residence in a given place was also important, and its type (town or a village) and size were less important. For half of the surveyed teachers, it was difficult for them to indicate the distinguishing feature (symbol) of their place of work, regardless of whether they were inhabitants or commuters from elsewhere.